Potential of Social Protection Policy Interventions for Breaking Poverty Cycle in Tanzania - Mwaijande, Francis; Mwakalikamo, Joshua (Journal of Social and Policy Issues, 2024)
The purpose of this article is to ascertain the theory of change that by providing income assistance, consumption transfers and empowerment interventions, the poor and vulnerable groups overcome risks of falling into extreme poverty. This article adopted a cross-sectional descriptive survey research design to assess the effect of social protection on outcome variables. Both probability and non-probability sampling techniques were used. A random selection of regions, districts and households was conducted for obtaining quantitative data. Whereas, non-probability sampling techniques of purposeful sampling was used for selecting key informants to provide qualitative and rich information on the studied social protection programmes. The sample size was 204 distributed into on-programme (102 households) and non-programme (102 households) in Tanga and Mtwara regions. Triangulation methods includes use of both quantitative and qualitative methods in data collection and analysis of before and after interventions to determine net effect of social protection policy. Productive Social Safety Net  is a Tanzania social protection policy intervention to overcome poverty to poor households. It  provides cash transfers to increase households’ income, health insurance to increase access to health services and economic empowerment to increase employment and income generating opportunities. The study results indicate positive significant (r=.159*, P<.05) relationship between Productive Social Safety Net (PSSN) and poverty reduction in Tanzania, results also proved positive significant (r = -.284**, p<=01) relationship between health insurance and poverty. This means implementing social protection policies reduces intergenerational poverty in the Sub-Saharan Africa.  These are triangulated with qualitative voices saying “ our group, we are able to buy equipment when we get funds from Economic empowerment, we buy hall and chairs. This enables us to get income. I use for food in my family “. As for NHIF, it helps when I go to hospital I see the doctor, I get medical treatment”. However,  no single social protection intervention can reduce poverty because poverty is multi-dimensional. While economic empowerment reduces income poverty through enabling job creation, income generation activities and asset building, productive social safety net enhances social capital to overcome intergenerational poverty through conditional cash-transfers on child education attendance and improved nutritional status. The article implies that multiple social protection interventions produce effect on poverty reduction based on the PSSN, health insurance and economic empowerment interventions in Tanzania.